Implementation of Business Competition Violation Norms in the Decision of the Business Competition Supervision Commission - Arifin Ma’ruf; Wahyu Beny Mukti Setiyawan; Widiatama Widiatama (Faculty of Law, Universitas Sebelas Maret, 2020)
This paper analyzes the application of norms concerning violations of business competition in KPPU decisions. The case study in this paper is in the case of violations of business competition conducted by PT Forisa Nusapersada in Case Decision Number 14/KPPU-L/2015. As a comparison, this study also compares the application of norms in cases that are almost similar, namely the Decision of the Case KPPU Number 14/ KPPU-L/ 2015 with the Decision of the Case KPPU Number: 06/KPPU-L/2004. The results of the research show that in addition to Article 19 and Article 25 above, KPPU should also apply Article 52 paragraph (2) letter a and Article 15 paragraph (3) of Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition in the case of PT Forisa Nusapersada.